Revealing the Potential Advantages of Plectasin Through In Vitro Rumen Fermentation Analysis - Qinwu Li; Baozhen Zhu; Fei Li; Zhiyuan Ma; Long Guo; Xiuxiu Weng (Fermentation)
Plectasin, a novel antimicrobial peptide, has the potential to disrupt bacterial cell walls and alter the rumen fermentation mode, making it a superior alternative to antibiotics. However, there is limited research on the effects of plectasin on rumen microbiota. This study aimed to evaluate the effects of plectasin (0.057 μmol/L) on in vitro rumen fermentation characteristics and select groups of rumen bacterial communities in comparison with monensin (5 μmol/L), one of the most commonly used ionophores in ruminants, and as a control treatment with the basal substrate. Unlike monensin, plectasin was found to increase the molar proportions of butyrate and acetate/propionate ratio (p < 0.001) while decreasing pH and the molar proportions of propionate (p < 0.05). Principal component analysis of bacterial 16S rRNA gene amplicons clearly showed a separation between the bacteria shaped by plectasin and monensin. Comparative analysis also revealed differences in the relative abundance of certain bacteria in different taxa between plectasin and monensin. The divergent effects of plectasin and monensin on bacterial communities are likely responsible for the differences in their ability to alter rumen fermentation. Plectasin may have advantages over monensin in modulating ruminal bacterial communities and increasing the butyrate and the acetate/propionate ratio. Therefore, it may be considered as a potential additive for ruminant feed.